Molecular Strategies for Improved Dielectric Elastomer Electrical Breakdown Strengths. Issue 16 (23rd July 2018) - Yu, Liyun; Skov, Anne L.
Abstract: Dielectric elastomer transducers (actuators and generators) possess great commercial potential because they allow for novel transducer designs and applications due to—amongst others—their flexibility and low weight. On the other hand, the flexibility and inherent softness of dielectric elastomers also pose restrictions on their use, since the thin elastomers may undergo destructive deformations under large loads or in large electrical fields. In order to design better dielectric elastomers, it is crucial to understand the underlying phenomena of how thin and elastic dielectric elastomer films undergo electrical breakdown. This understanding will allow for the design of dielectric elastomers with high electrical breakdown strength and thus open up the use of films in transducers at higher electrical fields and forces. Here, the study couples intrinsic electrical breakdown strengths with well‐described polymer and network characteristics, namely Kuhn parameters and cross‐linking density. The universality of the developed model is illustrated by comparison over a wide range of silicone‐based elastomers, such as prestretched elastomers and synthesized cross‐linked bottlebrush polymers, representing both filled and unfilled elastomers. This study paves a robust way for the molecular design of elastomers into high‐intrinsic electrical breakdown strength dielectric elastomers. Abstract : The low intrinsic electrical breakdown strength of soft silicone elastomers remains a challenge in the commercialization of dielectric elastomers. A theoretical model, employed to describe electrical breakdown strength based on the molecular structure of the polymer network structure, is developed and shows excellent predictions in relation to the electrical breakdown strengths of a wide range of silicone‐based dielectric elastomers.